2019
DOI: 10.1155/2019/7809171
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Fiber and Insoluble Fiber Regulate Colonic Microbiota and Barrier Function in a Piglet Model

Abstract: The main purpose of the present study was to assess the effect of soluble and insoluble fiber on colonic bacteria and intestinal barrier function in a piglet model. A total of 24 piglets (25 ± 1 d old; 7.50 ± 0.31 kg) were randomly allotted to 4 treatments: basal diet (control, CON), 1% insoluble dietary fiber (IDF) diet, 1% soluble dietary fiber (SDF) diet, and 0.5% insoluble fiber + 0.5% soluble dietary fiber (MDF) diet. The trial lasted 28 days. SDF-fed piglets showed a higher P<0.05 bacterial a-diversit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 59 publications
5
36
0
1
Order By: Relevance
“…Association between Prevotella spp. and dietary fiber, particularly insoluble dietary fiber, has been observed previously in piglets supplemented with 1% lignocellulose [ 56 ]. This same study also observed that 1% inulin reduces Prevotellaceae abundance compared with piglets fed either 1% insoluble fiber or a standard corn soy diet [ 56 ].…”
Section: Discussionmentioning
confidence: 90%
“…Association between Prevotella spp. and dietary fiber, particularly insoluble dietary fiber, has been observed previously in piglets supplemented with 1% lignocellulose [ 56 ]. This same study also observed that 1% inulin reduces Prevotellaceae abundance compared with piglets fed either 1% insoluble fiber or a standard corn soy diet [ 56 ].…”
Section: Discussionmentioning
confidence: 90%
“…In a healthy state, the pig and gastrointestinal microbiota share a symbiotic relationship that contributes to the nutrition and health of the pig, and in turn, the pig provides substrate for microbiota largely in the form of DF. However, all DF is not created equal and its efficacy to modulate microbial taxa, diversity, and composition is dependent on DF composition, solubility, and concentration [ 33 , 34 ]. In general, soluble DF and non-digestible oligosaccharides are fermented at a faster rate compared to insoluble DF [ 35 , 36 ] and are associated with reducing pathogenetic microbes, increasing microbial diversity, and improving the proliferation of ‘beneficial’ microbes [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The importance of the type of dietary fiber was recently demonstrated by Deehan et al 51 ; small discrete alterations in the chemical structure of fibers caused distinct enrichments of certain taxa, leading to altered metabolite output. More specifically, soluble fibers increase the alpha diversity and relative abundance of Proteobacteria and Actinobacteria, whereas insoluble fibers increase Bacteroidetes and Euryarchaeota, as well as IgA and tumor necrosis factor-alpha levels 52 . Thus, both human donor and murine recipient diets must be carefully assessed for desirable FMT outcomes.…”
Section: Influence Of the Human Donor's Diet And Exercise On The Gut mentioning
confidence: 97%